1992
DOI: 10.1530/acta.0.1260201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a two-hour early awakening and of bright light exposure on plasma patterns of cortisol, melatonin, prolactin and testosterone in man

Abstract: Bright light is a synchronizing agent that entrains human circadian rhythms and modifies various endocrine and neuroendocrine functions. The aim of the present study was to determine whether and how the exposure to a bright light stimulus during the 2 h following a 2 h earlier awakening could modify the disturbance induced by the the sleep deprivation on the plasma pattens of hormones whose secretion is sensitive to light and/or sleep, namely melatonin, prolactin, cortisol and testosterone. Six healthy and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Our results also contrast with studies that reported no effect of sleep deprivation on melatonin secretion (Jimerson et al, 1977; Touitou et al, 1992; von Treuer et al, 1996; Leproult et al, 1997; Goichot et al, 1998; Kudo et al, 1999; Redwine et al, 2000), and studies showing melatonin amplitude, but not phase, changes (Akerstedt et al, 1979; Salin-Pascual et al, 1988; Rao et al, 1996; Shilo et al, 1999; Goh et al, 2001; Cajochen et al, 2003). We cannot explain why the melatonin phase and amplitude results of our current study differ from our previous baseline studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results also contrast with studies that reported no effect of sleep deprivation on melatonin secretion (Jimerson et al, 1977; Touitou et al, 1992; von Treuer et al, 1996; Leproult et al, 1997; Goichot et al, 1998; Kudo et al, 1999; Redwine et al, 2000), and studies showing melatonin amplitude, but not phase, changes (Akerstedt et al, 1979; Salin-Pascual et al, 1988; Rao et al, 1996; Shilo et al, 1999; Goh et al, 2001; Cajochen et al, 2003). We cannot explain why the melatonin phase and amplitude results of our current study differ from our previous baseline studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of the effects of wake therapy on melatonin amplitude measures showed primarily no effect (Jimerson et al, 1977; Touitou et al, 1992; von Treuer et al, 1996; Leproult et al, 1997; Goichot et al, 1998; Kudo et al, 1999; Redwine et al, 2000), although some observed an increase (Akerstedt et al, 1979; Salin-Pascual et al, 1988; Goh et al, 2001), and some a decrease (Rao et al, 1996; Shilo et al, 1999; Cajochen et al, 2003). These disparate results may be due to different methodologies employed, including the timing and frequency of the melatonin measurements in relation to sleep deprivation, light and activity conditions, the use of plasma versus urinary or salivary measures, the duration and timing of the change in sleep phase or sleep deprivation, and the method used to analyze melatonin amplitude or phase.…”
Section: Introductionmentioning
confidence: 92%
“…In two studies, plasma PRL concentrations were increased, either during evening bright light [10] or after morning light exposure [27]. In others, PRL levels were unaffected by night light [28,29], and also after daily light exposure [30]. In some studies, PRL levels were suppressed by light at night [11,31].…”
Section: Discussionmentioning
confidence: 99%
“…Peak and trough times of testosterone have been shown to be erratic with serum concentrations signi¢cantly decreased. 57 Other reports show no obvious modi¢cations in testosterone concentration on exposure to bright light, 58 and the picture may be confounded by the in£uence of satisfaction or dissatisfaction with shift working since men dissatis¢ed with the pattern of work revealed lower testosterone concentrations. 59 …”
Section: Time Of the Day And Season Of The Yearmentioning
confidence: 96%